Asignación presupuestaria y su relación con el gasto de proyectos de inversión de la Municipalidad Distrital de Urarinas periodo 2019 – 2023 - Sampertegui Muñoz, Ken Arnold (2025)
Investment projects are a fundamental tool for reducing economic indicators such as poverty in Peru. However, the main issue in budget allocation and spending on investment projects in the municipalities within the Loreto region lies in the lack of transparency in the allocation and execution processes. This study aims to identify the relationship between budget allocation and spending on investment projects in the district municipality of Urarinas during the period 2019-2023. A correlational, quantitative, non-experimental design analysis was conducted. The study population consisted of budget records for allocation and spending on investment projects of the municipality. Data analysis reveals that the relationship between budget allocation and spending on investment projects in the district municipality of Urarinas during the period 2019-2023 is weak and not significant, with a Pearson correlation coefficient of 0.300 and a significance level of 0.624, contradicting the general hypothesis of a significant and positive relationship between these two aspects. Budget allocation showed significant variability throughout the studied period, with notable fluctuations and no clear positive trend, despite certain increases in specific years such as 2023 compared to 2022. On the other hand, spending on investment projects showed a constant decreasing trend from a peak in 2019, reaching its lowest point in 2023, indicating that the execution of these projects did not occur significantly nor with a positive trend. These findings suggest an urgent need to improve the management and execution of investment projects in Urarinas, highlighting deficiencies in their planning, execution, and monitoring, which could be hindering the economic and social development of the community.